Analysis of Covid-19 Using A Modified SEIR Model To Understand The Cases Registered in Singapore, Spain, And Venezuela - Isea, Raúl; Mayo-García, Rafael (Journal of Model Based Research, 2022)
This work proposes a modification of a compartmental-type model based on the Susceptible-Exposed-Infected-Recovered (SEIR) scheme to describe the dynamics of contagion by Covid-19 in any part of the world, including also the numerical and analytical calculation of the mantissa and the resolution of a partial differential equation system. As an example, the different incidents that occurred in Singapore, Spain and Venezuela are analyzed to demonstrate the usefulness of the methodology developed in this work that can be seamlessly extended to other regions.
Keywords: Covid-19; SEIR; Mantissa; Dynamics; Spain; Singapore; Venezuela